The web‐based self‐reported survey of Alcohol Use Disorders Identification Test and associated factors in Japan - Tomomi Toyama; Chie Nitta; Yoshiki Koga; Kaoru Hamanaka; Mitsuru Kimura; Sachio Matsushita (PCN Reports)
Abstract Aim While considerable data on the alcohol drinking behavior of the general population are available for the United States and Europe, data from Asian countries are scarce. We attempted to estimate the social backgrounds and other factors associated with high Alcohol Use Disorders Identification Test (AUDIT) scores in Japan. Methods This web‐based survey was conducted in 2023. In order to ensure the representativeness of the sample, the population distribution by age and region was determined from the Statistics Bureau Census Basic Population Summary. The survey questionnaire items included AUDIT, educational background, occupation, income, marital status, body mass index (BMI), age at the time of the first alcoholic drink, age at the start of habitual drinking, Kessler Psychological Distress Scale (K6), and Link's Devaluation Discrimination Scale. Results A total of 40,720 responses were received from people aged between 20 and 75 years old. The proportion of potential alcohol use disorder based on AUDIT score ≥15 was 9.2% in men and 2.0% in women. The number of people with AUDIT scores ≥15 tended to be high in men in their 50s and women in their 20s and 40s. Among those with AUDIT scores ≥15, the age at the first drink and age at the start of habitual drinking were significantly lower, and the K6 score was significantly higher. Conclusion This web survey showed an association between AUDIT scores and age at first drinking and mental health condition. Since this survey was a web‐monitored survey, caution should be taken in generalizing the prevalence.